Handbook of therapeutic storytelling : stories and metaphors in psychotherapy, child and family therapy, medical treatment, coaching and supervision /: stories and metaphors in psychotherapy, child and family therapy, medical treatment, coaching and supervision. (2018) - Hammel, Stefan
No abstract available